Viabilidade e perspectivas da cogeração e da geração termoeletrica junto ao setor sucro-alcooleiro - Walter, Arnaldo César da Silva, 1957- (1994)
Orientadores: Sergio Valdir Bajay, Luiz Augusto Horta Nogueira